Development of a computationally efficient semi-distributed hydrologic modeling application for soil moisture, lateral flow and runoff simulation. (November 2016) - Ajami, Hoori; Khan, Urooj; Tuteja, Narendra K.; Sharma, Ashish
Abstract: A new automated workflow based computationally efficient hydrologic modeling application is developed for soil moisture and runoff simulation. The spatially distributed conceptual framework underpinning the S oil M oisture A nd R unoff simulation T oolkit (SMART) resolves water balance in large upland catchments where topography and land cover are significant drivers of rainfall-runoff transformations. SMART's computational efficiency is achieved by delineation of contiguous and topologically connected hydrologic response units and solving the water balance equation on spatially representative Equivalent Cross-Sections (ECSs). ECSs are formulated by aggregating topographic and physiographic properties of the complete or part of the first order Strahler sub-basins, thereby reducing the number of computational elements. Water balance simulations across the ECSs in two sub-basins illustrated little loss of accuracy compared to the distributed cross section delineations and soil moisture observations. A 2-dimensional Richards' equation based hydrologic model in SMART can be augmented with additional functionalities or replaced with other model structures. Highlights: SMART is a new semi-distributed hydrologic modeling application applied to topologically connected HRUs. SMART workflow automates sub-basin, HRU and cross section or equivalent cross section delineations of the entire catchment. SMART reduces computational time of large catchment scale simulations by reducing the number of computational elements. Temporal dynamics of sub-basin soil moisture are reasonably captured using parameters obtained from soil and land cover data.